2019
DOI: 10.3847/1538-4357/ab2638
|View full text |Cite
|
Sign up to set email alerts
|

The Sloan Digital Sky Survey Reverberation Mapping Project: Accretion Disk Sizes from Continuum Lags

Abstract: We present accretion-disk structure measurements from continuum lags in the Sloan Digital Sky Survey Reverberation Mapping (SDSS-RM) project. Lags are measured using the JAVELIN software from the first-year SDSS-RM g and i photometry, resulting in well-defined lags for 95 quasars, 33 of which have lag SNR > 2σ. We also estimate lags using the ICCF software and find consistent results, though with larger uncertainties. Accretion-disk structure is fit using a Markov Chain Monte Carlo approach, parameterizing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 92 publications
8
90
0
Order By: Relevance
“…In addition, an inhomogeneous disk with significant local temperature fluctuations may also explain the larger disk sizes from microlensing studies (Dexter & Agol 2011). However, Mudd et al (2018) and Homayouni et al (2019) did not find systematic trends of larger disk sizes than the prediction of the thin-disk model. To address this discrepancy, more disk size measurements are required, especially using high-cadence time series data.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, an inhomogeneous disk with significant local temperature fluctuations may also explain the larger disk sizes from microlensing studies (Dexter & Agol 2011). However, Mudd et al (2018) and Homayouni et al (2019) did not find systematic trends of larger disk sizes than the prediction of the thin-disk model. To address this discrepancy, more disk size measurements are required, especially using high-cadence time series data.…”
Section: Introductionmentioning
confidence: 89%
“…The broad-line variability may consequently make the measured lag larger than the real continuum lag. We assess the contamination from broad emission lines as the ratio of the equivalent width of the emission line to the effective width of the broadband filter, referred to as f BLR , similar to Homayouni et al (2019). Those authors identified potential contamination if f BLR >12.5%.…”
Section: Javelin Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Variations in different bands are well coordinated. Changes of short-wavelength emission lead those of long-wavelength emission (e.g., Sergeev et al 2005;Fausnaugh et al 2016;Jiang et al 2017;Homayouni et al 2019;Cackett et al 2018;Kokubo 2018;McHardy et al 2018;Mudd et al 2018;Yu et al 2018;Edelson et al 2019). Current observations have a broad diversity of measured time lags beyond the SSD theory: some AGNs have time lags that are about three times larger than the flux-weighted light-travel time delays of the SSD theory.…”
Section: Agn Uv/optical Fractional Variability Amplitude In-mentioning
confidence: 98%